Human Multipotent Mesenchymal Stromal Cells in the Treatment of Postoperative Temporal Bone Defect: An Animal Model. Issue 7 (July 2016) - Skoloudik, Lukas; Chrobok, Viktor; Kalfert, David; Koci, Zuzana; Sykova, Eva; Chumak, Tetyana; Popelar, Jiri; Syka, Josef; Laco, Jan; Dedková, Jana; Dayanithi, Govindan; Filip, Stanislav
Canal wall down mastoidectomy is one of the most effective treatments for cholesteatoma. However, it results in anatomical changes in the external and middle ear with a negative impact on the patient's quality of life. To provide complete closure of the mastoid cavity and normalize the anatomy of the middle and external ear, we used human multipotent mesenchymal stromal cells (hMSCs), GMP grade, in a guinea pig model. A method for preparing a biomaterial composed of hMSCs, hydroxyapatite, and tissue glue was developed. Animals from the treated group were implanted with biomaterial composed of hydroxyapatite and hMSCs, while animals in the control group received hydroxyapatite alone. When compared to controls, the group implanted with hMSCs showed a significantly higher ratio of new bone formation ( p = 0.00174), as well as a significantly higher volume percentage of new immature bone ( p = 0.00166). Our results proved a beneficial effect of hMSCs on temporal bone formation and provided a promising tool to improve the quality of life of patients after canal wall down mastoidectomy by hMSC implantation.